The Influence of Biological Asset Accounting Policies and Corporate Governance Practices on the Financial Performance: Moderating Role of Knowledge about Renewable Energy - Retno Martanti Endah Lestari (International Journal of Energy Economics and Policy, 2020)
High financial performance is the primary goal of all companies, including agricultural companies. In practice, the impact caused by various problems related to accounting policies of biological assets, principles of good corporate governance, knowledge about renewable energy and size of the company. This study aims to prove empirically whether there is an influence of biological asset accounting policy implications, good corporate governance practices and company size on financial performance along with the moderating role of knowledge about renewable energy in agricultural sector companies. Research data were collected through questionnaire instruments, face-to-face interviews and group discussion forums which were conducted in several places in Indonesia by sampling with non-probability sampling. Data were analyzed using Structural Equation Model (SEM). The results showed that the implications of biological asset accounting policies, good corporate governance practices and company size had positive effects on financial performance and knowledge about renewable energy is playing a moderating role among the links. The plantation and forestry sector which is the unit of analysis is a limitation of this study because the agricultural industry includes not forests and gardens, but livestock and fisheries are also included in those who have biological transformed assets. Keywords: Biological Asset Accounting Policies, Good Corporate Governance, Company Size, Financial Performance, Knowledge about Renewable Energy JEL Classifications: K32, G30, Q DOI: https://doi.org/10.32479/ijeep.10240